MANAGEMENT OF WAQF ASSETS AT THE GREAT MOSQUE OF SEMARANG: A MAQASID AL-SHARI'AH PERSPECTIVE - Ahmad Wahyudi; Achmad Arief Budiman; Bagas Heradhyaksa; Wawaysadhya (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2026)
The management of the bandha wakaf (endowment assets) of Masjid Agung Semarang (MAS) faces structural complexity resulting from its long history of land exchanges, the duality of legal status among tanah bondo, waqf land, and properties registered under external names, as well as overlapping institutional authorities. This study aims to describe the current management practices of MAS based on primary interview data and secondary documentary sources and to analyze them through the lens of Maqasid al-Shariah with a particular focus on the preservation of property (ḥifẓ al-māl) and the promotion of public benefit (al-maṣlaḥah al-‘āmmah). The findings show that although several assets have not yet been legally secured, the management employs pragmatic strategies, including developing productive business units, regulating relations with occupants of the assets, and securing the properties through land mapping, physical markers, and identification signage. The maqasid-based analysis reveals that these measures align with the objective of safeguarding waqf assets from loss while ensuring their benefit for the congregation and the broader community. The resulting model may be characterized as “maqasid pragmatism,” a welfare-oriented management approach for waqf amid structural limitations of formal legal frameworks. This study enriches the scholarly discourse on productive waqf management and proposes a maqasid-based evaluative approach for addressing contested waqf assets in Indonesia. Keywords: waqf assets, Masjid Agung Semarang, Maqasid al-Shariah, ḥifẓ al-māl, public benefit